Anti-inflammatory, antidiabetic and antibacterial activities, ADMET analysis, in silico toxicity prediction, and molecular docking study of N-ferrocenylmethyl-nitroaniline and N-ferrocenylmethyl-N-nitrophenyl- 4-nitrobenzamide - Bekkar, Yahia (University Of Eloued جامعة الوادي, 2025)
This thesis presents a comprehensive evaluation of several ferrocenyl derivatives, including Ferrocenylmethyl-aniline (FMA), Ferrocenylmethyl-m-toluidine (3FMT), and their acylated derivatives synthesized in VTRS laboratory. The study investigates their potential as therapeutic agents through both in vitro and in silico approaches, focusing on their antidiabetic, anti-inflammatory, and antibacterial activities. The new synthesized compounds, 3FMT and its acylated derivatives, were characterized using UV-Vis spectroscopy, electrochemistry, IR, and NMR techniques, which confirmed their proposed structures. Antidiabetic activity was evaluated through interactions with α-amylase, revealing significant inhibitory effects of the ferrocenyl derivatives, with binding energy (∆G) values ranging from -24.1 to -34.78 kJ/mol and IC50 values between 0.69 and 64.5 µM. For anti-inflammatory activity was assessed through interactions with bovine serum albumin (BSA), showing that all compounds except FMA and 3FMT, effectively inhibited BSA denaturation, with IC50 values ranging from 1.72 to 7.26 µM and ∆G between -33.36 and -31.06 kJ/mol. These results indicate that all acylated compounds exhibit a stronger antidiabetic and anti-inflammatory compared the standard drug acarbose (IC50 of 259 µM) and diclofenac (IC50 of 15.81 µM). The antibacterial activity of these compounds was assessed against E. coli, S. aureus, K. pneumoniae, and P. aeruginosa, revealing moderate to strong antibacterial effects. However, their effectiveness was generally lower than that of amoxicillin, which demonstrated superior inhibition across all strains. Molecular docking studies also corroborated these findings, demonstrating strong binding affinities of the compounds to α-amylase (ΔG between -5.85 and -7.84 kcal/mol), BSA (ΔG between -8.04 and -10.49 kcal/mol), and COX-2 (ΔG between -8.17 and -11.97 kcal/mol). For the antibacterial. Regarding antibacterial mechanisms, the ferrocenyl derivatives primarily targeted Peptidoglycan D,D-transpeptidase in P. aeruginosa and Penicillin-binding protein 2a in S. aureus. Additionally, some compounds interacted with Dihydrofolate reductase and DNA gyrase subunit B in S. aureus, Anthranilate-CoA ligase and Peptide deformylase in both P. aeruginosa and E. coli, and DNA topoisomerase IV in K. pneumoniae. These results suggest that the ferrocenyl derivatives, particularly the acylated ones, have significant potential as inhibitors in antidiabetic, anti-inflammatory, and antibacterial pathways. Furthermore, quantum chemical calculations supported their stability and interactions within the active sites of these proteins, reinforcing their potential as promising therapeutic agents الملخص: تقدم هذه الأطروحة تقييماً شاملاً لعدة مشتقات فيروسينيلية، بما في ذلك فيروسينيل ميثيل أنيلين(FMA) ، فيروسينيل ميثيل-3-تولويدين (3FMT) و مشتقاتها الأسيلية التي تم تصنيعها في المختبر. تستكشف الدراسة إمكاناتها كعوامل علاجية من خلال نهج مزدوج يشمل الاختبارات داخل المختبر (in vitro) والمحاكاة الحاسوبية (in silico)، مع التركيز على أنشطتها المضادة لمرض السكري، والمضادة للالتهابات، والمضادة للبكتيريا. تمت دراسة المركبات الجديدة، 3FMT ومشتقاتها الأسيلية، باستخدام تقنيات التحليل الطيفي بالأشعة فوق البنفسجية-المرئية (UV-Vis)، والكهروكيمياء، والأشعة تحت الحمراء(IR) ، والرنين المغناطيسي النووي(NMR) ، مما أكد البنية المقترحة لهذه المركبات. تم تقييم النشاط المضاد لمرض السكري من خلال دراسة تفاعلات المركبات مع إنزيم ألفا أميلاز، حيث أظهرت المشتقات الفيروسينيلية تأثيرات تثبيطية قوية، إذ تراوحت طاقة الارتباط (ΔG) بين 24.1- و34.78- كيلوجول/مول، وسُجلت قيم IC50 بين 0.69 و64.5 ميكرومول. كما تم تقييم النشاط المضاد للالتهابات عبر دراسة التفاعلات مع ألبومين مصل الأبقار (BSA)، حيث لوحظ أن جميع المركبات، باستثناء FMA و3FMT، تثبط بشكل فعال عملية تفكك البروتيني (Dénaturation) لـ BSA، مع قيم IC50 تراوحت بين 1.72 و7.26 ميكرومول وطاقة ارتباط ΔG بين 33.36- و31.06- كيلوجول/مول. تشير هذه النتائج إلى أن جميع المركبات الأسيلية تتمتع بفعالية مضادة لمرض السكري ومضادة للالتهابات تفوق العقاقير المرجعية، مثل الأكاربوز (IC50 =259 ميكرومول) والديكلوفيناك (IC50 =15.81 ميكرومول). تم تقييم النشاط المضاد للبكتيريا لهذه المركبات ضد سلالات بكتيرية شملت القولونيات المعوية (E. coli)، العنقوديات الذهبية (S. aureus) ، و الكلبسيلا الرئوية(K. pneumoniae) ، والزائفة الزرقاء (P. aeruginosa) ، حيث أظهرت المركبات تأثيرات مضادة للبكتيريا تراوحت بين المتوسطة والقوية. ومع ذلك، كانت فعاليتها عمومًا أقل من الأموكسيسيلين، الذي أظهر تثبيطًا أقوى ضد جميع السلالات. أكدت دراسات الإرساء الجزيئي (Molecular Docking) هذه النتائج، حيث أظهرت المركبات مستويات عالية من الارتباط مع ألفا أميلاز (ΔG بين 5.85- و7.84- كيلوكالوري/مول)، BSA (ΔG بين 8.04- و10.49- كيلوكالوري/مول)، وCOX-2 (ΔG بين 8.17- و11.97- كيلوكالوري/مول). فيما يتعلق بالآليات المضادة للبكتيريا، استهدفت المشتقات الفيروسينيلية بشكل رئيسي إنزيم ناقلة الببتيدوغليكان (D,D-transpeptidase) في الزائفة الزنجارية، وبروتين ارتباط البنسلين أ2 في المكورات العنقودية الذهبية. كما أظهرت بعض المركبات تفاعلات مع إنزيم مختزل ثنائي هيدروفولات والوحدة الفرعية ب لأنزيم التفاف الحمض النووي (DNAgyrase) في المكورات العنقودية الذهبية، بالإضافة إلى إنزيم ليغاز أنثرانيلات-مرافق الإنزيم A (Anthranilate-CoA ligase) وإنزيم إزالة الفورميل من الببتيد (Peptide deformylase) في كلٍّ من الزائفة الزنجارية والإشريكية القولونية. أما في الكلبسيلة الرئوية، فقد استهدفت المركبات إنزيم توبويزوميراز (DNA topoisomerase IV)، مما يشير إلى آليات متعددة لمكافحة العدوى البكتيرية. تشير هذه النتائج إلى أن المشتقات الفيروسينيلية، لا سيما الأشكال الأسيلية منها، تمتلك إمكانات قوية كمثبطات في المسارات المضادة لمرض السكري، والمضادة للالتهابات، والمضادة للبكتيريا. علاوة على ذلك، أكدت الحسابات الكيميائية الكمومية ثبات هذه المركبات وقدرتها على التفاعل داخل المواقع النشطة لهذه البروتينات، مما يعزز إمكاناتها كعوامل علاجية واعدة.
Thesis
Keywords: : Ferrocenyl derivatives; Antidiabetic activity; Anti-inflammatory activity; antibacterial activities; BSA; α-Amylase; Molecular docking; DFT; مشتقات الفيروسين; النشاط المضاد لمرض السكري; النشاط المضاد للالتهابات; النشاط المضاد للبكتيريا; ألفا أميلاز; الإرساء الجزيئي